Ecommunity : a mobile e-waste community framework - Ahmad Fesol, Siti Feirusz (2014)
The utilization of electronics in our everyday life is almost as important as our very existence in this fast-paced globalized world, but the effective management and long term effects of the resultant waste has not fully been grasped by consumers. As reported by UNEP, 20 to 50 million metric tonnes of e-waste are generated worldwide every year are comprising more than 5 percent of all municipal solid waste and approximately less than 25 percent out of these amount of e-waste being recycle. The remaining of e-waste are either stockpiled in garages, closets or when thrown away they end up in landfills or incinerators and more recently they are exported to Asia. In order to highlight this concern, the purpose of this research is to figure out the level of awareness among the community in practicing proper e-waste management. The research case study will take place in Universiti Teknikal Malaysia Melaka (UTeM). This study will review and analyse the level of knowledge and awareness from the perspective of UTeM community which include the staffs and students, in handling their e-waste. There are two main approaches which are combination of qualitative and quantitative techniques being implemented in this research in order to get the most accurate result. From the result gathered, a mobile social communication framework for e-waste management will be proposed which function as a platform to inform, alert and update the community on the issues with regards to e-waste. This system aimed able to educate and increase the awareness among the community in taking care of their environment.